Real-World Experience With Ceftazidime-Avibactam for Multidrug-Resistant Gram-Negative Bacterial Infections. (6th December 2019) - Jorgensen, Sarah C J; Trinh, Trang D; Zasowski, Evan J; Lagnf, Abdalhamid M; Bhatia, Sahil; Melvin, Sarah M; Steed, Molly E; Simon, Samuel P; Estrada, Sandra J; Morrisette, Taylor; Claeys, Kimberly C; Rosenberg, Joshua R; et al.
Abstract: Background: We conducted this study to describe the clinical characteristics, microbiology, and outcomes of patients treated with ceftazidime-avibactam (CZA) for a range of multidrug-resistant Gram-negative (MDR-GN) infections. Methods: This is a multicenter, retrospective cohort study conducted at 6 medical centers in the United States between 2015 and 2019. Adult patients who received CZA (≥72 hours) were eligible. The primary outcome was clinical failure defined as a composite of 30-day all-cause mortality, 30-day microbiological failure, and/or failure to resolve or improve signs or symptoms of infection on CZA. Results: In total, data from 203 patients were evaluated. Carbapenem-resistant Enterobacteriaceae (CRE) and Pseudomonas spp were isolated from 117 (57.6%) and 63 (31.0%) culture specimens, respectively. The most common infection sources were respiratory (37.4%), urinary (19.7%), and intra-abdominal (18.7%). Blood cultures were positive in 22 (10.8%) patients. Clinical failure, 30-day mortality, and 30-day recurrence occurred in 59 (29.1%), 35 (17.2%), and 12 (5.9%) patients, respectively. On therapy, CZA resistance developed in 1 of 62 patients with repeat testing. Primary bacteremia or respiratory tract infection and higher SOFA score were positively associated with clinical failure (adjusted odds ratio [aOR] = 2.270, 95% confidence interval [CI] = 1.115–4.620 and aOR = 1.234, 95% CI = 1.118–1.362, respectively). Receipt of CZA within 48 hours of infection onset was protective (aOR, 0.409; 95% CI, 0.180–0.930). Seventeen (8.4%) patients experienced a potential drug-related adverse effect (10 acute kidney injury, 3 Clostridioides difficile infection, 2 rash, and 1 each gastrointestinal intolerance and neutropenia) Conclusions: Ceftazidime-avibactam is being used to treat a range of MDR-GN infections including Pseudomonas spp as well as CRE.